Analysis of The Impact of Environment, Discipline, and Work Motivation on The Performance of Employees of Employees in The Education Office of West Java Province - Budi Susilo; Deden Sutisna (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyze the effects of the work environment, work discipline, and work motivation on employee performance at the West Java Provincial Education Office. The study was motivated by the declining organizational performance achievement, which decreased from 82.17% in 2020 to 78.92% in 2024, accompanied by increasing employee tardiness and several work environment and motivation issues identified through a preliminary survey. These conditions indicate the need to examine factors influencing employee performance in the public sector. This research employed a quantitative approach with descriptive and verification methods. Data were collected through questionnaires distributed to 166 employees and analyzed using multiple linear regression. The results show that the work environment, work discipline, and work motivation each have a positive and significant effect on employee performance, both partially and simultaneously. Work motivation emerged as the most dominant variable influencing employee performance (β = 0.292). Furthermore, the coefficient of determination (R²) value of 0.164 indicates that 16.4% of the variation in employee performance can be explained by the three independent variables, while the remaining 83.6% is influenced by other factors outside the model. These findings imply that improving employee motivation, strengthening disciplinary practices, and creating a supportive work environment are essential strategies for enhancing employee performance and achieving organizational objectives more effectively.